Studies on Chromene based 2, 6-disubstituted-Thiazolo [3,2-B] [1,2,4] Triazole derivatives: Synthesis and Biological Evaluation - Naseer, Md Arif; Husain, Asif (Journal of Drug Delivery and Therapeutics, 2019)
In this study, a series of novel chromene based 2,6-disubstituted-thiazolo[3,2-b] [1,2,4] triazole derivatives (7a-g) were synthesized by condensing 5-substituted-1,2,4-traizole-thione (6a-g) using poly phosphoric acid through one pot reaction. The structure of new compounds was supported by 1H NMR, 13C NMR and MS data. The synthesized compounds were evaluated using writhing assays for analgesic and carrageenan-induced rat paw edema method for anti-inflammatory activities respectively. Some of the newly synthesized compounds 7c, 7f and 7g showed very good anti-inflammatory activity with 90.83%, 85.81% and 88.40% protection respectively along with low GI toxicity as compared to standard drug ibuprofen while compounds 7a, 7b, 7d and 7f showed highest analgesic activity with 52.54%, 54.02%, 56.76% and 52.45% protection among them compound 7d showed better protection than standard drug ibuprofen.Keywords: thiazolo-triazoles, Chromene, Anti-inflammatory, Analgesic